PENGEMBANGAN FLASHCARD BERBANTUAN WORDWALL MENGGUNAKAN MODEL PBL UNTUK MENINGKATKAN HARGA DIRI SISWA KELAS III SEKOLAH DASAR KABUPATEN BLITAR - Aulia Rizka Fariani; Mohamad Fatih; Khoirul Wafa (Global Action and Education for Society, 2026)
The purpose of this study was to develop Wordwall-integrated flashcard materials to enhance IPAS learning and raise third-grade students' self-esteem at SDN 3 Candirejo, Blitar Regency. The researcher used a mixed-approaches approach, combining a quantitative methodology with research and development (R&D) directed by the ASSURE model. After the development process, a media prototype was created and verified by media and subject matter experts. Questionnaires, interviews, and observation were used to collect data, which were then subjected to descriptive quantitative analysis. A 95% score from content experts indicated a high level of validity, and an 85.71% score from media experts indicated a similarly high level of validity. The control group's significant values were less than 0.007 according to the Paired Sample T-test.